Cayaponia silva manso (cucurbitaceae juss.), no estado de Goiás: uma abordagem morfológica e anatômica - Cardoso Junior, Ilvan Martins (2017)
Cayaponia Silva Manso (Cucurbitaceae Juss.), In the State of Goiás: a morphological and anatomical approach - Cayaponia Silva Manso comprises about 60 species of which 47 occur in Brazil. Several studies have been carried out with species of this genus in view of the proven pharmacological potential for some taxa, mainly C. tayuya (Vell) Cogn., C. martiana (Cogn.) Cogn. In Goiás it was reported the existence of seven species that constitute two groups that are differentiated respectively by the habits and habitats where they are found, one formed by the species C. espelina (Silva Manso) Cogn., C. rugosa Gomes-Klein et Pirani and C. weddellii (Naudin) Cogn. And the other group comprising the species C. tayuya (Vell.) Cogn., C. citrullifolia (Griseb.) Cogn., C. diversifolia (Cogn.) Cogn. and C. podantha Cogn. Some studies have been carried out to solve complexes in other botanical families. Studies on the anatomy of vegetative and reproductive organs have presented results that contribute to a better circumscription for the species under study. In this work, morphological, taxonomic and anatomical studies were carried out with the objective of adding new information that allows a better delimitation and recognition of the studied species. A preliminary survey of information on Cayaponia species occurred in the State of Goiás. 41 expeditions were carried out in 42 municipalities. Specimens of 7 species were collected in the State of Goiás. For the morphological and taxonomic studies, the collected material was processed, herborized and identified according to the usual methodology. For the anatomical analysis part of the material was preserved fresh in a freezer at 10 ° C, another part fixed in alcohol70, in FAA70 or FPA70. In Chapter 1 the taxonomic treatment for the species occurring in Goiás was carried out. A key of identification, morphological and taxonomic description was presented, as well as illustrations of the species studied. In Chapter 2 the description of foliar architecture of the species under study was presented. Also in this chapter an identification key was developed for the species under study based on foliar architecture and venation patterns. Chapter 3 presents anatomical analyzes of petiole and leaf blade, scanning electron microscopy and histochemical tests that were used in the separation of taxa. Statistical tests, Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) were applied with the objective of performing a prospection of morpho-anatomic characters that support the groups delimited in previous chapters.